The Impact Of Brand Dimension On The Purchasing Decision Making Of The Smartphone In Indonesia - Syafaat, Yogi, Ihwan Susila, SE., M.Si., Ph.D (2017)
This paper explores the impact of brand dimension on purchasing decision making of the Smartphone in Indonesia. This study aims to determine the influence of such brand dimension on purchasing decision and to reveal which is the most influential. Data were collected using questionnaire-based survey consisting of 32 questions and distributed to 120 respondents comprising all of smartphone consumer in Indonesia city Solo and Ngawi. In order to analyze the data obtained from questionnaires, quantitative methods were employed. The findings showed that perceived quality and country of origin have a significant effect on purchasing decision, and marketing communication and historical tradition insignificant on purchasing decision. Finally, the study recommends that manager should improve the purchase decision making for gain high customer.